PLGA nanoparticle formulations of risperidone: preparation and neuropharmacological evaluation - Muthu M.S.; Rawat M.K.; Mishra A.; Singh S. (My University, 2025)
The aim of this work was to develop extended-release poly(d,l-lactide-co-glycolide) (PLGA) nanoparticles of risperidone and thermal-responsive in situ gel containing risperidone nanoparticles for parenteral (subcutaneous) delivery and to reduce the dose-dependent extrapyramidal side effects of risperidone. PLGA nanoparticles of risperidone were designed by nanoprecipitation method using polymeric stabilizer (Poloxamer 407). The prepared nanoparticles were characterized for particle size by photon correlation spectroscopy and atomic force microscopy. Poloxamer 407-based in situ gel containing PLGA nanoparticles of risperidone was prepared by modified cold method to control the initial rapid release from the nanoparticles. The in vivo efficacy (antipsychotic effect) of prepared formulations (nanoparticles and in situ gel containing nanoparticles) was studied by administering them subcutaneously to mice. Extrapyramidal side effects of the formulations were also studied. The particle size of the prepared nanoparticles ranged between 85 and 219 nm. About 89% to 95% drug encapsulation efficiency was achieved when risperidone was loaded at 1.7% to 8.3% by weight of the polymer. During in vivo studies prepared risperidone formulations showed an antipsychotic effect that was significantly prolonged over that of risperidone solution for up to 72 hours with fewer extrapyramidal side effects. The prolonged effect of risperidone was obtained from the risperidone formulations administered subcutaneously, and this may improve the treatment of psychotic disorders by dose reduction. From the Clinical Editor: The development of extended-release poly(d,l-lactide-co-glycolide) (PLGA) nanoparticles of risperidone is reported in this paper, along with the development of thermal-responsive in situ gel containing risperidone nanoparticles for parenteral (subcutaneous) delivery and to reduce the dose-dependent extrapyramidal side effects. In vivo studies showed a significantly prolonged antipsychotic effect with fewer extrapyramidal side effects. © 2009 Elsevier Inc. All rights reserved.